2007
DOI: 10.1111/j.1399-3054.2006.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy amongst photosynthetic acclimation responses for plant fitness

Abstract: We have compared the seed production of Arabidopsis wild‐type and mutant plants impaired in the regulation of the photosynthetic light reactions grown under natural conditions in the field. Mutant plants (npq4) lacking feedback de‐excitation were, as previously demonstrated, severely affected in seed production. Seed sets of plants deficient in state transitions (stn7) were 19% smaller than those of wild‐type plants, whereas plants missing the STN8 kinase required for the phosphorylation of the core photosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 18 publications
5
81
1
Order By: Relevance
“…In flowering plants, however, the physiological significance of state transitions is less clear because their mobile LHCII pools are significantly smaller than those in green algae (Allen, 1992;Delosme et al, 1994). Moreover, plant development and fitness are only marginally affected in A. thaliana mutants impaired in state transitions (Lunde et al, 2000;Bonardi et al, 2005;Tikkanen et al, 2006), even under fluctuating light (Bellafiore et al, 2005) or field conditions (Frenkel et al, 2007) when the ability to adapt to illumination changes should become crucial. Therefore, it has been speculated that state transitions play a less prominent role in land plants than in green algae (Finazzi et al, 2002;Finazzi, 2005), becoming important only under low light conditions (Tikkanen et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In flowering plants, however, the physiological significance of state transitions is less clear because their mobile LHCII pools are significantly smaller than those in green algae (Allen, 1992;Delosme et al, 1994). Moreover, plant development and fitness are only marginally affected in A. thaliana mutants impaired in state transitions (Lunde et al, 2000;Bonardi et al, 2005;Tikkanen et al, 2006), even under fluctuating light (Bellafiore et al, 2005) or field conditions (Frenkel et al, 2007) when the ability to adapt to illumination changes should become crucial. Therefore, it has been speculated that state transitions play a less prominent role in land plants than in green algae (Finazzi et al, 2002;Finazzi, 2005), becoming important only under low light conditions (Tikkanen et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The interpretation of qE is possibly the most complex of the NPQ components, as it is linked to faster regulation of photosynthesis than qT and qI with most organisms, especially under naturally fluctuating environment (Lavaud 2007). Frenkel et al (2007) demonstrated that qE is critical for maintaining the fitness of plants under natural temperate-light conditions, rather than qT. Also, in cyanobacteria and green microalgae, qT has no significant physiological importance in photoprotection towards high-light stress, yet is more relevant in low light conditions (Mullineaux and Emlyn-Jones 2005;Ruban and Johnson 2009) and for acclimation to different light quality (Pfannschmidt 2005).…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 99%
“…Only a relatively small fraction of the LHCII antenna (,20%) is estimated to participate in state transitions in Arabidopsis (Arabidopsis thaliana; Allen, 1992). However, the process is conserved across the green eukaryotes and is relevant to plant fitness (Frenkel et al, 2007). Under high light, energy-dependent quenching of LHCII predominates, and furthermore, this antenna can uncouple from PSII (Wientjes et al, 2013b).…”
mentioning
confidence: 99%